Ofloxacin resistance in multibacillary new leprosy cases from Purulia, West Bengal: a threat to effective secondary line treatment for rifampicin-resistant leprosy cases. (September 2022) - Ahuja, Madhvi; Singh, Itu; Lavania, Mallika; Pathak, Vinay Kumar; Darlong, Joydeepa; Turankar, Ravindra P; Hembrom, S.; Singh, Shoor Veer; Sengupta, Utpal
Highlights: Rifampicin, a bactericidal drug, is the backbone of multidrug therapeutic regimens, and it is important to monitor the emergence of rifampicin-resistant strains of leprosy. The World Health Organization recommends an alternate regimen (Ofloxacin + Minocycline + Clofazimine) for rifampicin-resistant cases, which is safe and effective. This situation is alarming for patients who are already resistant to ofloxacin. There is an urgent need to develop alternate regimens for such cases. ABSTRACT: Objectives: Purulia is one of the high-endemic districts for leprosy in West Bengal (the eastern part of India). The annual new case detection rate (ANCDR) of leprosy in West Bengal is 6.04/100000 (DGHS 2019–20). Our earlier report provided evidence of secondary drug resistance in relapse cases of leprosy. The aim of the current study was to observe primary drug resistance patterns for dapsone, rifampicin, and ofloxacin amongst new leprosy patients from Purulia, West Bengal in order to better understand the emergence of primary resistance to these drugs. Methods: In the present study, slit-skin smear samples were collected from 145 newly diagnosed leprosy cases from The Leprosy Mission (TLM) Purulia hospital between 2017 and 2018. DNA was extracted from these samples and the Mycobacterium leprae genome was analyzed for genes associated with drug resistance by polymerase chain reaction (PCR), followed by Sanger sequencing. Wild-type strain (Thai-53) and mouse footpad-derived drug-resistant strain (Z-4) were used as reference strains. Results: Of 145 cases, 25 cases showed mutations in genes associated with resistance to rifampicin, dapsone, and ofloxacin (as described by the World Health Organization, rpoB, folP, and gyrA, respectively) through Sanger sequencing. Of these 25 cases, 16 cases showed mutations in ofloxacin, two cases showed mutations in combinations of ofloxacin and rifampicin, four cases showed a mutation only in rifampicin, one case showed mutations in combinations of rifampicin and dapsone, and two cases showed mutations only in dapsone. Conclusion: Results from this study indicated the emergence of resistance to antileprosy drugs in new cases of leprosy. As ofloxacin is the alternate drug for the treatment of rifampicin-resistant cases, the emergence of new cases with resistance to ofloxacin indicates that ofloxacin-resistant M. leprae strains are actively circulating in this endemic region (i.e., Purulia, West Bengal), posing challenges for the effective treatment of rifampicin-resistant cases.